Impact of Social Media on Customer Loyalty: A Mixed Study on Moroccan Companies - ELOUAZZANI Lamiaa; CHAKOR Abdellatif (Revue Internationale du Chercheur, 2025)
Social media has fundamentally changed the marketing landscape by acting as a dynamic platform that influences how consumers discover, evaluate, and purchase products or services. This study investigates the impact of social media interactions on the customer-brand relationship, focusing on their role in fostering long-term loyalty and driving purchasing decisions. Employing a mixed-method research design, the study collected data through qualitative interviews with marketing managers from six companies and a quantitative online survey administered to 460 customers. The findings highlight that social media creates opportunities for personalized content, real-time engagement, and interactive communication, all of which significantly contribute to strengthening customer trust, brand affinity, and repeat buying behaviors. By leveraging features such as customized advertising and targeted promotions, companies can effectively encourage users to transition from casual followers to dedicated brand advocates. However, the research also acknowledges potential limitations, including the representativeness of the chosen sample and the possibility of response bias in self-reported data. Based on these insights, businesses are urged to allocate resources strategically to social media marketing initiatives and to adopt tailored approaches that address specific cultural, economic, and market conditions. Social media emerges as an indispensable tool for building lasting customer loyalty and enhancing overall brand performance.